(3GJMGa aVdGA GdRef HJGQjN hdGjI Hfi GdMSfs - (3GHf GdeMH GdWHQj , eMeO Hf Ydj Hf aVd Hf YHO Gddg GHf GdeMH GdWHQjs ((3GdWhHLi eMeO SYjO Hf eMeO Hf SdjeGf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi HYK ef GdMQe eMeOkGhZeGekG GeG HYO, ajbhd GdabjQ Edi Gddg GdTGaYi Gf Ghdi eG GfJgJ Edjg Gdgee GdYdjG s
(3BNQgG (B:s
(3hhUd eY GdML GdePchQ ai fLO hSei GdSjO UGdM hai djdg GdNejS NGeS YGThQ JQMd GdML GdYQGbi hhba bde GdeDda s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B296 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B34s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B7 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs